Associations between combined exposure to environmental hazards and social stressors at the neighborhood level and individual perinatal outcomes in the ECHO-wide cohort. (July 2022) - Martenies, Sheena E.; Zhang, Mingyu; Corrigan, Anne E.; Kvit, Anton; Shields, Timothy; Wheaton, William; Bastain, Theresa M.; Breton, Carrie V.; Dabelea, Dana; Habre, Rima; Magzamen, Sheryl; Padula, Amy M.; et al.
Abstract: Limited studies examine how prenatal environmental and social exposures jointly impact perinatal health. Here we investigated relationships between a neighborhood-level combined exposure (CE) index assessed during pregnancy and perinatal outcomes, including birthweight, gestational age, and preterm birth. Across all participants, higher CE index scores were associated with small decreases in birthweight and gestational age. We also observed effect modification by race; infants born to Black pregnant people had a greater risk of preterm birth for higher CE values compared to White infants. Overall, our results suggest that neighborhood social and environmental exposures have a small but measurable joint effect on neonatal indicators of health. Highlights: We assessed combined exposure to environmental and social stressors in a national cohort. Greater exposure was associated with lower birthweight and gestational age. Greater exposure was associated with higher risk of preterm birth. Exposure effects were modified by pregnant person race, educational attainment, and urbanicity.